Vascular Dementia and Underlying Sex Differences - Akhter, Firoz; Persaud, Alicia; Zaokari, Younis; Zhao, Zhen; Zhu, Donghui (Frontiers in Aging Neuroscience, 2021)
Vascular dementia (VaD) is the second most common form of dementia after Alzheimer’s disease (AD); where Alzheimer’s accounts for 60-70% of cases of dementia and VaD accounts for 20% of all dementia cases. VaD is defined as a reduced or lack of blood flow to the brain that causes dementia. VaD is also known occasionally as vascular contributions to cognitive impairment and dementia (VCID) or multi-infarct dementia (MID). VCID is the condition arising from stroke and other vascular brain injuries that cause significant changes to memory, thinking, and behavior, and VaD is the most severe stage while MID is produced by the synergistic effects caused by multiple mini strokes in the brain irrespective of specific location or volume. There are also subtle differences in the presentation of VaD in males and females, but they are often overlooked. Since 1672 when the first case of VaD was reported until now, sex and gender differences have had little to no research done when it comes to the umbrella term of dementia in general. This review summarizes the fundamentals of VaD followed by a focus on the differences between sex and gender when an individual is diagnosed. In addition, we provide critical evidence concerning sex and gender differences with a few of the main risk factors of VaD including pre-existing health conditions and family history, gene variants, aging, hormone fluctuations, and environmental risk factors. Additionally, the pharmaceutical treatments and possible mitigation of risk factors is explored.